Innate and mild Th17 cutaneous immune responses elicited by subcutaneous infection of immunocompetent mice with Cladosporium cladosporioides. (February 2022) - Ma, Xiaoping; Hu, Jing; Wang, Chengdong; Gu, Yu; Cao, Sanjie; Huang, Xiaobo; Wen, Yiping; Zhao, Qin; Wu, Rui; Zuo, Zhicai; Yu, Shumin; Shen, Liuhong; et al.
Abstract: Cladosporium cladosporioides is a dematiaceous hyphomycete that is pathogenic in the superficial and deep tissues of both immunodeficient and immunocompetent humans and animals. Our aim was to evaluate the antifungal immune responses elicited by C. cladosporioides in immunocompetent mice. Hence, we subcutaneously injected suspensions of C. cladosporioides spores into immunocompetent mice to investigate the anti-fungal immune responses in the skin. We collected skin tissue samples for histopathological examination, immunofluorescence staining, and quantitative real-time polymerase chain reaction analysis. We observed subcutaneous abscesses in mice after subcutaneous injection of C. cladosporioides . A large number of inflammatory cells, including dendritic cells, macrophages, and neutrophils, infiltrated the focal abscess, with comparatively few infiltrating inflammatory cells in the epidermal and dermal layers of the skin. We detected the expression of CD54 in the abscesses and the skin. Gene expression of the pattern recognition receptors Dectin-1 and TLR-2 was higher in infected mice than in controls. Gene expression of the cytokines IL-6, IL-1β, and IL-17A also increased after infection, suggesting that the Th17 signaling pathway may be involved in the anti-fungal response. Although the pathogenicity of C. cladosporioides in healthy mice was weak after subcutaneous infection, resulting in few serious pathological phenomena, it appears that innate and Th17 immune responses play important roles in the cutaneous host response to C. cladosporioides . These findings lay a foundation for further study of the pathogenic mechanism and treatment of C. cladosporioides infection. Highlights: Cladosporium cladosporioides does not easily cause serious skin infection in healthy mice. Expression of IL-6, IL-1β, and IL-17A increased upon injection of C. cladosporioides . The innate immune system played a key role in controlling C. cladosporioides in the skin.